Integralni i multimodalni transport u sredstvima zračnog prometa - Radačić, Željko; Suić, Ivan (Promet - Traffic&Transportation)
Specific aspects of air transport as a unique engineering, technological, management and economic complex dynamic system in particular its specific engineering and technological features have conditioned a specific resolution of the requirements regarding the speed and efficiency of completion of the transport process and the requirements regarding the reduction of costs by introduction of all modern transport technologies characterized with inclusion of technical means and devices between the transportation means and freight for purposes of introduction of unit loads (freight) and concentration of freight (pallets and containers. Palletization and containerization of freight transported by aircraft have been accommodated lo technical and technological characteristics of transportation means in air transport so that consequently the circulation of pallets and containers used in air transport is mostly completed inside the system of air transport.